Ca(II)-catalyzed diastereoselective formal [4+2] annulation of a 3-component solvent-free povarov reaction. Issue 15 (11th April 2019) - Khaja Mohinuddin, P. Md.; Dada, Ravikrishna; Almansour, Abdulrahman I.; Arumugam, Natarajan; Yaragorla, Srinivasarao
Graphical abstract: Highlights: Diastereoselective annulation reaction. One-pot, solvent-free reaction. Cascade-[4+2] annulation and aromatization. Eco-friendly catalyst with a high natural abundance. Extension to terminal acetylenes as dienophiles. Abstract: Diastereoselective, three-component annulation reaction involving glyoxals, anilines and dienophiles is developed under calcium catalysis. When indene is the dienophile, the reaction gave excellent diastereoselectivity to yield tetrahydro-indenoquinolines, these were further aromatized to get indenoquinolines in one-pot. Aryl acetylenes are used as dienophiles to get 2-acyl quinolines in good yields.